Physioacoustic economy at optimum frequency - Shashikala (Journal of All India Institute of Speech and Hearing, 1970)
Present study was aimed at finding out the physioacoustic economy at the optimum frequency as located by an objective method of locating optimum pitch as described by Nataraja (1972). The intensity range, maximuln phonation duration, mean airflow rate were measured in 5 male and 5 female subjects with good voice, at optimum frequency, 50 Hz above optimum frequency, 100 Hz optimum frequency, 200 Hz above optimum frequency and 50 Hz below optimum ,frequency. The frequency range was also measured to know the locatio!n of optimum frequency in the frequency range.